Agenda riset masa depan advertising berbasis AI melalui Analisis Bibliometrik dan Analisis Tematik - Loso Judijanto; Muhamad Ammar Muhtadi (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2026)
The development of artificial intelligence has driven significant transformations in digital advertising practices, in terms of marketing strategy, data analytics, and creative content production. However, the increase in AI-based advertising research still shows a fragmented pattern, requiring comprehensive mapping to understand the knowledge structure and future research development direction. This study aims to map the scientific landscape and formulate a future research agenda for AI-based advertising through a bibliometric analysis and thematic analysis approach. Research data was obtained from the Scopus database and analyzed using VOSviewer software to identify keyword networks, author collaborations, institutions, and countries. The results show that artificial intelligence, marketing, and advertising are the core concepts that connect various research themes, with a shift in trends towards generative AI, large language models, and content automation. Network visualization also reveals the dominance of several actors and countries in scientific collaboration, although opportunities for interdisciplinary research development remain wide open. Overall, this study provides a conceptual contribution by offering a map of knowledge structures as well as a direction for future research agendas that emphasize technology integration, marketing strategies, and ethical considerations in AI-based advertising.